Generic Promotion of Norwegian Whitefish Exports. Issue 2 (15th March 2021) - Williams, Gary W.; Capps, Oral
Abstract: The Norwegian Seafood Council (NSC) works to develop demand for Norwegian seafood exports. This study addresses two questions: (1) What have been the effects of NSC generic export promotion programs on the Norwegian whitefish export volume, price, and value? (2) Has the Norwegian whitefish industry benefited from its investment in generic export promotion? The study concludes that NSC generic export promotion added 11% to the export value of Norwegian whitefish between 2003 and 2017 from an addition to the export price and volume of 6% and 2%, respectively. About 10% of industry profits was due to the generic export promotion yielding an industry profit benefit-to-cost ratio of 5.9.